Isolation and characterization of microsatellite loci in the stingless bee Melipona interrupta manaosensis (Apidae: Meliponini) - Francini, Izaura Bezerra; Sousa, Adna Cristina Barbosa; Sforça, D. A.; Costa-Pinto, M. F.F.; Campos, Tatiana de; Nunes-Silva, Carlos Gustavo; Zucchi, Maria Imaculada; Souza, A. P. de; Carvalho-zilse, Gislene Almeida (Conservation Genetics Resources, 2010)
Melipona interrupta manaosensis is an important pollinator in the Neotropics. This stingless bee is reared by locals for honey production and also for conservation purposes. Eleven microsatellite markers were isolated from M. i. manaosensis and characterized in 32 individuals from the Meliponary of the Instituto Nacional de Pesquisas da Amazônia, Manaus, AM, Brazil. The number of alleles observed for each locus ranged from 2 to 5 (average 2.77). The polymorphism information content (PIC) varied between 0.08 to 0.62 (average 0.34) and the discriminating power (D) ranged from 0.61 to 0.99 (average 0.85). The observed heterozygosity (H O) and the expected heterozygosity (H E) ranged from 0.04 to 1.00 and 0.04 to 0.67, respectively. These microsatellites will be useful for future genetic studies of M. i. manaosensis populations and correlated species contributing with Amazon biodiversity preservation. © Springer Science+Business Media B.V. 2009.
Keywords: Apidae; Melipona; Meliponinae